Simultaneous Improvement in Photovoltaic Performance and Air Stability of Perovskite Solar Cells by Controlling Molecular Orientation of Spiro-OMeTAD - Nuttaya Sukgorn; Anusit Kaewprajak; Sasiphapa Rodbuntum; Navaphun Kayunkid; Nopporn Rujisamphan; Chatree Saiyasombat; Kouki Akaike; Pisist Kumnorkaew (My University, 2024)
2,2′,7,7′-Tetrakis (N,N-di-p-methoxyphenyl-amine)9,9′-spirobifluorene (Spiro-OMeTAD) is a prototypical hole transport layer (HTL) for high-performance perovskite solar cells (PSCs). Since the electric conductivity of a neat Spiro-OMeTAD film is low, the HTL is generally doped with additives to increase charge density and mobility. However, the doped Spiro-OMeTAD film suffers from moisture absorption, which deteriorates the long-term stability of PSCs. This work reports that the molecular orientation of Spiro-OMeTAD molecules in the doped HTL is vital to solving this issue. Templating the molecular arrangement of Spiro-OMeTAD by a solidifying solvent, 1,3,5-trichlorobenzene (135-TCB), forms an anisotropic film of the doped Spiro-OMeTAD and induces a face-on orientation along the surface normal. Modifying the molecular orientation enhances hole mobility in the HTL and extraction of holes at the perovskite/HTL interface. As a result, the maximum power conversion efficiency (PCE) of the PSCs increases from 17.63 to 19.92%. Besides, the air stability of the PSCs with the face-on Spiro-OMeTAD, after storage for 1000 h, is superior to that of the devices without templating the molecular arrangement of Spiro-OMeTAD by 135-TCB. Control of the molecular orientation of Spiro-OMeTAD is critical for improving PCE and air stability.
Keywords: Perovskite Materials and Applications